SIMULASI RUTE PENGIRIMAN PRODUK NESTLE CARNATION PT KARTIKA DISTRINDO DENGAN MENGGUNAKAN METODE CAPACITATED VEHICLE ROUTING PROBLEM - Natalia Hartono; Laurence Laurence; Melvin Pangestu (Journal Industrial Manufacturing, 2017)
Kartika Distrindo is a distribution company with various types of product. The high cost of distribution is the problem for Kartika Distrindo which caused they don’t have fix distribution route, to minimize distribution cost they need to makes new distribution route using capacitated vehicle routing method. Using historical data can be obtained average velocity, work hours, and distribution cost, those data are used to perform simulations using AIMSS software. The additional data for perform simulation are location data, distance between location, and delivery processing time. The result of distribution cost simulation data will be compared with distribution historical data. The conclusion is the reduce distribution cost from Rp 11.561.260 to Rp 6.048.918 or 47,7%, and reduce of car use from 5 to 3 and 2 car.Keywords: Capacitated Vehicle Routing Problem, Distribution, Optimization, AIMMS Software.